2022
DOI: 10.3390/medicina58020281
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Papilledema Following Ventriculoperitoneal Shunt or Endoscopic Third Ventriculostomy for Obstructive Hydrocephalus: A Pilot Study

Abstract: Background and Objectives: Ventriculoperitoneal Shunt (VPS) and Endoscopic Third Ventriculostomy (ETV) are both gold standard procedures to reduce intracranial pressure (ICP) in patients with obstructive hydrocephalus, which often results in papilledema. This comparative study was carried out at the Department of Neurosurgery of Dhaka Medical College and Hospital to compare the efficacy of VPS and ETV in the resolution of papilledema in 18 patients with obstructive hydrocephalus. Materials and Methods: The suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Hemorrhagic hydrocephalus and neoplastic hydrocephalus are two common types of secondary hydrocephalus [ 3 , 4 ]. Early diagnosis of secondary hydrocephalus is of great significance to guide clinical treatment and improve the prognosis of patients [ 5 , 6 ]. We used to rely on typical symptoms and signs and imaging examination to distinguish between hemorrhagic hydrocephalus and neoplastic hydrocephalus [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhagic hydrocephalus and neoplastic hydrocephalus are two common types of secondary hydrocephalus [ 3 , 4 ]. Early diagnosis of secondary hydrocephalus is of great significance to guide clinical treatment and improve the prognosis of patients [ 5 , 6 ]. We used to rely on typical symptoms and signs and imaging examination to distinguish between hemorrhagic hydrocephalus and neoplastic hydrocephalus [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Van Gompel et al identified both hypothalamic changes on MRI T2WI and the irregular enhancement as pre-operative predictors of higher-grade hypothalamic involvement [ 20 ]. Hayashi et al reported that the degree of the extent of the peritumoral hypothalamic edema on coronal FLAIR and T2WI MRI images could be an index of the pre- and postoperative functional outcome in adult patients [ 22 , 32 , 33 ]. Indeed, the authors found that patients with focal hypothalamic edema in MRI (group B) or extensive edema in the optic tract and internal capsule (group C) presented a worse outcome than those without edema (group A).…”
Section: Discussionmentioning
confidence: 99%
“…One of the advantages of this non-invasive technology over DBS is that it can target cortical and subcortical structures; therefore, it can reach remote locations from the stimulation site [ 96 , 98 ]. It should also be mentioned that DBS is an invasive procedure, consequently, it goes hand in hand with some complications, such as infection, limited duration of electrical components, neural immune system reactions, and the need for periodic battery replacement [ 99 , 100 , 101 , 102 ]. One of the limitations of TMS is that this device is large and heavy, whereas tDCS is light and small, which makes it more feasible since it is a treatment that does not require hospitalization and the sessions can be performed at the patient’s home [ 97 , 103 ].…”
Section: Non-invasive and Minimally Invasive Treatmentmentioning
confidence: 99%